Healthcare utilization for inpatient rehabilitation among people with traumatic brain injury before the introduction of the specialized rehabilitation hospital system: a nationwide retrospective cohort study - Bae, Suk Won; Shin, Jiyoung; Park, Wha Me; Kim, Jeongha (Frontiers in Neurology, 2025)
IntroductionIn this study, we aimed to examine the use of inpatient rehabilitation services among individuals who experienced a traumatic brain injury (TBI) in 2017, before the establishment of the specialized rehabilitation hospital system.MethodsWe analyzed healthcare resource utilization among patients hospitalized with TBI at acute care hospitals in 2017. Data were obtained from the National Health Insurance Service-Nationwide Health Insurance Database of South Korea. For patients who received inpatient rehabilitation, the length of stay (LOS) over the 2 years following their initial hospital admission was analyzed. Negative binomial regression was used to identify factors influencing LOS.ResultsPatients who received inpatient rehabilitation were hospitalized for a mean of 145.2 days during the follow-up period [median: (Q1–Q3): 35 (16–141) days]. LOS was shorter in tertiary hospitals, general hospitals, primary hospitals, and clinics than in long-term care hospitals (LTCHs) (all p < 0.001). After discharge from the initial healthcare institution, the most common first transfer destination was LTCH (27.5%), followed by general and primary hospitals. For subsequent hospitalizations, approximately half (48.3%) of the patients were admitted to LTCHs.ConclusionThese findings underscore the need to establish a specialized rehabilitation hospital system.